Eksistensi dan Pola Pendidikan Islam melalui Majelis Taklim di Perkantoran - Robiatul Adawiyah (Universitas Muhammadiyah Mataram, 2024)
Abstract: The individual attitudes and busy work schedules of urban communities make Islamic teaching increasingly necessary as an effort to strengthen spirituality in the current modern era. One way to get Islamic teaching is through the presence of a taklim assembly in the office. So it is important to carry out this research to see and analyze the existence and patterns of Islamic teaching in taklim assemblies held in urban offices. This research includes qualitative research using a case study method located at KPP Pratama Jakarta Gambir Dua. Data collection techniques use observation, interviews and documentation studies. The instruments used are semi-structured interview sheets and observation sheets. The data analysis technique uses descriptive analysis. The results obtained are (1) The taklim assembly is divided into two, namely the taklim assembly for male employees, female employees; (2) The teaching pattern of the taklim assembly at KPP Pratama Jakarta Gambir Dua for male and female employees has several differences which are adapted to the needs of each employee; (3) The existence of taklim assemblies in urban office environments (KPP Pratama Jakarta Gambir Dua) has an important role as a means of religious education, spiritual formation for employees, and as a forum for strengthening synergy and friendship between employees.Abstrak: Sikap individual dan kesibukan kerja masyarakat perkotaan, menjadikan pendidikan Islam semakin dibutuhkan sebagai upaya dalam penguatan spiritualitas di tengah era modern saat ini. Pendidikan Islam bisa didapatkan salah satunya dengan hadirnya majelis taklim di perkantoran. Maka penelitian ini penting dilakukan untuk melihat dan menganalisis eksistensi serta pola pendidikan Islam di majelis taklim yang diselenggarakan di kantor perkotaan. Penelitian ini termasuk penelitian kualitatif dengan metode studi kasus yang berlokasi di KPP Pratama Jakarta Gambir Dua. Teknik pengumpulan data menggunakan observasi, wawancara, dan studi dokumentasi. Dengan instrumen yang digunakan berupa lembar wawancara secara semi terstruktur dan lembar observasi. Teknik analisis data menggunakan analisis deskriptif. Hasil yang didapatkan adalah (1) Majelis taklim terbagi menjadi dua yaitu majelis taklim untuk pegawai laki-laki pegawai perempuan; (2) Pola pendidikan majelis taklim di KPP Pratama Jakarta Gambir Dua untuk pegawai laki-laki dan perempuan memiliki beberapa perbedaan yang disesuaikan dengan kebutuhan masing-masing pegawai; (3) Eksistensi majelis taklim di lingkungan perkantoran perkotaan (KPP Pratama Jakarta Gambir Dua) memiliki peran penting sebagai sarana pendidikan agama, pembinaan spiritual untuk para pegawai, dan sebagai wadah untuk mempererat sinergi dan silaturahmi antar pegawai.